2011
DOI: 10.1136/thoraxjnl-2011-200154
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of smoking behaviours in patients with COPD

Abstract: Background Cigarette smoking is a major risk factor for COPD and COPD severity. Previous genome-wide association studies (GWAS) have identified numerous single nucleotide polymorphisms (SNPs) associated with the number of cigarettes smoked per day (CPD) and a Dopamine Beta-Hydroxylase (DBH) locus associated with smoking cessation in multiple populations. Objective To identify SNPs associated with lifetime average and current CPD, age at smoking initiation, and smoking cessation in COPD subjects. Methods GW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 41 publications
5
84
1
4
Order By: Relevance
“…However, it is also possible that these genetic loci influence smoking behaviors via separate mechanisms that differentially impact levels of CO versus number of cigarettes smoked per day (e.g., influencing responses to nicotine in the initiation of smoking behaviors versus promoting more intense smoking of individual cigarettes and increased tolerance to smoking's aversive effects) (41,42). The existence of separable mechanisms influencing levels of CO versus amount smoked is consistent with findings that the CHRNA6-CHRNB3 locus shows little contribution to the genetic risk of COPD and lung cancer in the large-scale studies (43,44).…”
Section: Original Researchsupporting
confidence: 68%
“…However, it is also possible that these genetic loci influence smoking behaviors via separate mechanisms that differentially impact levels of CO versus number of cigarettes smoked per day (e.g., influencing responses to nicotine in the initiation of smoking behaviors versus promoting more intense smoking of individual cigarettes and increased tolerance to smoking's aversive effects) (41,42). The existence of separable mechanisms influencing levels of CO versus amount smoked is consistent with findings that the CHRNA6-CHRNB3 locus shows little contribution to the genetic risk of COPD and lung cancer in the large-scale studies (43,44).…”
Section: Original Researchsupporting
confidence: 68%
“…25 The tobacco and genetics consortium did a meta-analysis totalling 74 053 subjects and found DBH rs3025343 [G] is associated with smoking cessation. 26 Siedlinski et al 27 reported the genome-wide study of chronic obstructive pulmonary disease. They could replicate the result by the above consortium; that is, there was an association between a candidate genotype rs3025343 and smoking cessation in their subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[P ¼ 0.03, minor allele frequency (MAF) ¼ 0.04, imputation r 2 0.3-0.4 using HapMap2 data] previously described in this cohort as associated with lifetime average cigarettes per day (26), and rs36012476 in ADCK4 (P ¼ 0.02, MAF ¼ 0.07, and imputation r 2 0.6-0.7). Inclusion of these SNPs only modestly attenuated the signal for rs7937 (P after adjustment ¼ 8.3 × 10 28 ).…”
Section: Resultsmentioning
confidence: 99%